A randomized, endoscopist-blinded, prospective trial to compare the preference and efficacy of four bowel-cleansing regimens for colonoscopy. (July 2014) - Kim, Eun Sun; Lee, Woo Jin; Jeen, Yoon Tae; Choi, Hyuk Soon; Keum, Bora; Seo, Yeon Seok; Chun, Hoon Jai; Lee, Hong Sik; Um, Soon Ho; Kim, Chang Duck; Ryu, Ho Sang
Abstract Objectives. The superiority of conventional polyethylene glycol (PEG) solution over sodium picosulfate with magnesium citrate (SPMC) for bowel preparation remains controversial. Therefore, this study compared the efficacy, safety, and tolerability of different regimens of SPMC and PEG solution in Koreans, who consume a traditional high-fiber diet. Materials and methods. A total of 200 outpatients undergoing elective colonoscopy were randomized into four groups receiving different bowel-preparation regimens in a prospective study: 4 L PEG in the morning on the day of colonoscopy, two 2 L split doses of PEG, split doses of 2 SPMC sachets, and split doses of 3 SPMC sachets. Bowel cleansing efficacy was assessed based on the Ottawa bowel preparation scale and the Aronchick scale by endoscopists blinded to treatment, and patients filled out a questionnaire to determine satisfaction. Results. There was no difference among groups with respect to bowel cleansing grade (Ottawa scale, p = 0.314). Patients in the SPMC groups were less likely to have abdominal fullness, pain, nausea, or vomiting than patients in the PEG groups (p < 0.05). Patients reported SPMC was more palatable than PEG. There were no significant differences among groups with respect to polyp detection rate. Conclusion. SPMC is as effective as conventional high-volume PEG–electrolyte solution in Korean patients. SPMC groups reported superior palatability and tolerability compared to PEG groups.